Kikuchi-Fujimoto disease in the right cervical lymph node: a case report & literature review - Jung, Sang-Hwan; Jang, Han-Seul; Jang, Seong-Baek; Kwon, Tae-Geon; Choi, So-Young (The Korean Journal of Oral and Maxillofacial Pathology, 2019)
Histiocytic necrotizing lymphadenitis (Kikuchi-Fujimoto disease, KFD) is a benign self-limiting lesion that can self-heal when no severe symptoms are present. KFD resembles tuberculous lymphadenitis and malignant lymphoma. Thus, early differential diagnosis will minimize unnecessary evaluation and treatment. Histological examination of a lymph node biopsy or fine needle aspiration could be a reliable method for KFD diagnosis. This study reports a case of histiocytic necrotizing lymphadenitis of the right cervical lymph node in a 52-year-old female patient. According to the fine needle aspiration biopsy result, the patient was diagnosed with Kikuchi-Fujimoto disease and treated with prednisolone (15 mg/day). After treatment, there was no recurrence or adverse event. KCI Citation Count: 0